The molecular characterisation of methicillin-resistant Staphylococcus aureus from hospitals in Cape Town - Jansen van Rensburg, Melissa Jane (Department of Medicine, 2015)
Comprehensive molecular epidemiological data are prerequisite for establishing control over methicillin-resistant S. aureus (MRSA) in the hospital setting; however, there is currently a paucity of molecular epidemiological data available on MRSA from South Africa. A molecular characterisation of one hundred MRSA isolates collected between January 2007 and December 2008 from patients in five hospitals in Cape Town was carried out in this study.